Climatic growing conditions of Jatropha curcas L - Maes, W.H.; Trabucco, Antonio; Achten, W.M.J.; Muys, B. (Elsevier, 2009)
The massive investment in new jatropha plantations worldwide is not sufficiently based on a profound scientific knowledge of its ecology. In this article, we define the climatic conditions in its area of natural distribution by combining the locations of herbarium specimens with corresponding climatic information, and compare these conditions with those in 83 jatropha plantations worldwide. Most specimens (87%) were found in tropical savannah and monsoon climates (Am, Aw) and in temperate climates without dry season and with hot summer (Cfa), while very few were found in semi-arid (BS) and none in arid climates (BW). Ninety-five percent of the specimens grew in areas with a mean annual rainfall above 944 mm year1 and an average minimum temperature of the coldest month (Tmin) above 10.5 C. The mean annual temperature range was 19.3-27.2 C. The climatic conditions at the plantations were different from those of the natural distribution specimens for all studied climatic variables, except average maximum temperature in the warmest month. Roughly 40% of the plantations were situated in regions with a drier climate than in 95% of the area of the herbarium specimens, and 28% of the plantations were situated in areas with Tmin below 10.5 C. The observed precipitation preferences indicate that jatropha is not common in regions with arid and semi-arid climates. Plantations in arid and semi-arid areas hold the risk of low productivity or irrigation requirement. Plantations in regions with frost risk hold the risk of damage due to frost.